THE EFFECT OF EXTRINSIC MOTIVATION AND INSTRINSIC MOTIVATION AGAINST LEARNING ACHIEVEMENTS OF FOOD AND BEVERAGE SERVICE STUDENT AK. MAPINDO, ACADEMIC YEAR 2018/2019 - EKADHARMA SUSILA, BAGUS PUTU; ARIANTINI, NI PUTU OKA (Jurnal Manajemen Pelayanan Hotel, 2019)
This study aims to determine the effect of extrinsic motivation and instrinsic motivation on learning achievement students in the Food and Beverage Service Program Study, Akademi Komunitas Manajemen Perhotelan Indonesia academic year 2018/2019. The questionnaire distributed to 57 respondents was all members of the population. This study, using regression analysis techniques by testing hypotheses using t test and F test. The t-test results show that extrinsic motivation has a positive and significant effect on student achievement in the Food and Beverage Service Program Study, Akademi Komunitas Manajemen Perhotelan Indonesia academic year 2018/2019. This is seen from the results of the regression coefficient X1(b1) thitung = 6.977 > ttable (0.05: 54) = 1.6736 and sig t = 0,000 (p < 0.05). Intrinsic motivation has a positive and significant effect on student learning achievement in the Food and Beverage Service Program Study, Akademi Komunitas Manajemen Perhotelan Indonesia academic year 2018/2019. This is seen from the results of the regression coefficient X1(b1) thitung = 3.743> ttable (0.05: 54) = 1.6736 and sig t = 0,000 (p <0.05). Extrinsic motivation and intrinsic motivation have a positive and significant effect on student achievement in the Dish Study Program, Indonesian Hospitality Management Community Academy academic year 2018/2019. This is based on the results of the F statistical test (ANOVA) where Fcount = 32.521 > F table = 3.17 with sig F = 0,000 (p < 0.05). Other information obtained from the results of the above analysis that extrinsic motivation has a more dominant influence on learning achievement when compared with intrinsic motivation Keywords: Extrinsic Motivation, Intrinsic Motivation, Learning Achievement